PENGARUH LATIHAN LINGKARAN SPRINT TERHADAP KEMAMPUAN MENGGIRING BOLA PADA PEMAIN SEPAKBOLA SSB WONER 2012 PEKANBARU - Hafiz Kurniatama; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this study is that when dribbling is less than the maximum which causes a lack of ability to dribble quickly and lack of ability to dribble properly. This type of research is a type of experimental research to see the effect of the form of exercise. The purpose of this study was to look at the effect of Sprint Circle Exercise on the Ability of Dribbling in the 2012 Pekanbaru SSB Football Player. The population in this study is the 2012 SSB Woner players, amounting to 15 people. The sampling technique is to use total sampling, where the total population is sampled. Data collection techniques were obtained from pre-test and post test. The instrument in this study used all parts of the foot for dribbling the ball as a tool to measure the ability to dribble quickly with changes in direction. After that, the data is processed statistically, to test normality using a liliefours test at a significant level of 0.05α. Based on the analysis of the normality of the data X, it gives a LoMax of 0.1403 and a Ltable of 0.220, meaning LoMax <Ltable. while Y variable yields LoMax of 0.0992 and Ltable of 0.220. This means LoMax <LTabel. The analysis was performed using t-test. based on data analysis and discussion, it can be concluded that the effect of Sprint Circle Exercise on the Ability of Dribbling on the 2012 SSB Woner Soccer Player Pekanbaru is proven with a Tcount of 6.298 and a Table of 1.796. Means Thitung> Ttabel. At the level ɑ = 0.05.Key Words: Sprint loop training, dribbling ability